Evaluasi Sistem Informasi Akuntansi Penjualan Kredit - Ayu Apriyanti (COSTING : Journal of Economic, Business and Accounting, 2019)
Sales accounting information system is a system that is useful as a control tool for the implementation of a company's transactions. This research was conducted with the aim to find out how the credit sales information system in PD. Sinar Mas Hakasima Branch Jember, to find out how-not-the credit sales accounting information system has been done well. The analytical method used in this study is descriptive qualitative. Data collection techniques, interview techniques, observation / observation and documentation. The data used are primary data consisting of the results of direct interviews regarding credit sales accounting information systems. Based on the results of the analysis conducted by researchers, it can be seen that the credit sales accounting information system applied by PD. The Masasasima Branch of Jember Branch in processing credit sales transactions is good, the company has a good and adequate information system. Keywords: Accounting Information Systems, Credit Sales, Accounting Information System Elements